Functional Activity and Morphological Structure of Endocrine Glands at Different Level of Mineral Consumption - A. Menkova, Anna; A. Kazimirova, Tatyana; N. Bobkova, Galina; V. Malyavko, Ivan; V. Kubyshkin, Andrey (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the results of the functional morphology of the thyroid gland in heifers grown on diets with macro and micro element deficiency and with the optimal level of mineral consumption. The aim of the study was to evaluate the morphology of the thyroid gland in heifers grown on diets with macro- and micro-element deficiency and with an optimal level of mineral consumption. Methods of the study: histochemical, biochemical, laboratory, zootechnic, and statistical. The performed study showed that the optimization of macro- and micro-element diets of the replacement heifers led to moderate activation of the function of the thyroid gland, which provided a more intensive growth of the body and organs and an optimal time of reproductive and physiological maturation of animals.